Morphological characterization and performance of different pineapple (Ananas comosus) varieties in northern parts of West Bengal - BHOWMICK, NILESH; DEB, PRAHLAD; MUNSI, PARTHASARATHI; KR GHOSH, SWAPAN (The Indian Journal of Agricultural Sciences, 2022)
Pineapple [Ananas comosus (L.) Merr.] is popular all over the world for its pleasant aroma, sweet-acidic taste and smooth pulp texture. It is the third most important fruit on the basis of global trade after banana and citrus. The present investigation was carried out in 2014–16 to assess the growth behaviour and performance of different pineapple varieties like Kew, Queen, Mauritius, Haricharanvita, Baruipur Local, MD-2, MTS, and Amritha in northern parts of West Bengal. The experiment was laid in Randomized Block Design (RBD) for successive two years. The indigenous Haricharanvita variety showed the maximum vigour in terms of plant height, leaf length and canopy spread. The maximum numbers of leaves were recorded in Kew followed by Queen. Maximum leaf area was also recorded in Kew and the maximum numbers of suckers were produced by Mauritius followed by Baruipur Local. Mauritius exhibited earliest (325.75 days) and maximum flowering (98.34%), required lowest time (109.45 days) for maturity compared to all varieties assessed. Indigenous Haricharanvita and Baruipur Local exhibited delayed and lesser flowering percentage with longest fruit maturity time. Highest yield (without crown) was recorded in Kew (89.70 t/ha), followed by Mauritius (57.54 t/ha), while it was lowest in Baruipur Local (31.00 t/ha). Among the physico-chemical parameters, Mauritius recorded highest pulp percentage (62.70%), TSS (18.10obrix), total sugar (12.87%), ascorbic acid (45.52 mg/100g) content, TSS: acid ratio (28.14) and lowest peel (17.82%) and crown (17.79%) content. Among the different varieties studied, Mauritius was found to be the best table purpose variety under northern part of West Bengal